2001
DOI: 10.1016/s1097-2765(01)00364-1
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of Stable mRNA Fragments and Translation of N-Truncated Proteins Induced by Antisense Oligodeoxynucleotides

Abstract: Binding of phosphorothioate-modified antisense oligodeoxynucleotides (AS ODNs) to target mRNAs is commonly thought to mediate RNA degradation or block of translation. Here we demonstrate cleavage of target mRNAs within the AS ODN binding region with subsequent degradation of the 5' but not the 3' cleavage product. Some, if not all, 3' mRNA fragments lacked a 5' cap structure, whereas their poly(A) tail length remained unchanged. Furthermore, they were efficiently translated into N-terminally truncated proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 40 publications
2
33
1
1
Order By: Relevance
“…6E). The ability of similarly cleaved transcripts to be translated as functionally distinct proteins has been previously reported (Thoma et al 2001;Hasselblatt et al 2005;Snider et al 2009). Although an N-terminal proteomics study, analogous to the 59-terminal transcriptomic analysis conducted here, is required to determine the full contribution of this process to protein diversity, examination of publicly available N-terminal peptide sequences reveals an enrichment of peptides with N-terminal methionine downstream from cleavage sites relative to random positions in the coding sequence (Supplemental Fig.…”
Section: Post-transcriptional Cleavage Generates a Diversity Of Long mentioning
confidence: 82%
See 2 more Smart Citations
“…6E). The ability of similarly cleaved transcripts to be translated as functionally distinct proteins has been previously reported (Thoma et al 2001;Hasselblatt et al 2005;Snider et al 2009). Although an N-terminal proteomics study, analogous to the 59-terminal transcriptomic analysis conducted here, is required to determine the full contribution of this process to protein diversity, examination of publicly available N-terminal peptide sequences reveals an enrichment of peptides with N-terminal methionine downstream from cleavage sites relative to random positions in the coding sequence (Supplemental Fig.…”
Section: Post-transcriptional Cleavage Generates a Diversity Of Long mentioning
confidence: 82%
“…Although such long RNAs may ultimately be cleaved into smaller RNAs, we propose that truncated mRNA isoforms may also potentially be translated to C-or N-terminal truncated proteins. There are numerous precedents to support this proposal (Thoma et al 2001;Hasselblatt et al 2005;Snider et al 2009). For example, a recent study found that a range of endogenous small and long RNA transcripts are generated from the DUX4 gene, including a 39-cleaved isoform that undergoes translation from an internal methionine to generate a functionally distinct truncated protein that lacks the N-terminal domain (Snider et al 2009).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…4B, lanes 8 and 9) or together (data not shown). Inhibition was specific, as reprobing the same Western blot showed no changes in the level of either GAPDH or ␣-tubulin, and long exposures of the Western blot failed to detect truncated ASA protein, as can happen with antisense oligodeoxynucleotides (data not shown) (28). It was also possible that the anti-ASA U1 snRNAs were inhibiting expression by inducing aberrant splicing.…”
Section: Effects Of Increased Distance Multiple Binding Sites and Imentioning
confidence: 88%
“…This means that the mRNA encoding Mos could itself play a role in the meiotic maturation and that its integrity is required. The degradation of Mos mRNA could, for example, lead to the release of regulatory RNA-binding proteins or generate new stable mRNA fragments encoding for N-terminal truncated proteins, 64 which proteins could dramatically interfere with meiotic maturation. 63 Although not necessary for GVBD, Mos remains a powerful inducer of meiotic maturation when microinjected.…”
Section: The Role Of Mos Synthesismentioning
confidence: 99%